KEPATUHAN WAJIB PAJAK ORANG PRIBADI DITINJAU DARI TRANSPARANSI INFORMASI, MODERNISASI TEKNOLOGI PELAYANAN PAJAK DAN SANKSI PAJAK - Marieta Ariani; Syamsurizal Syamsurizal (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
This research aims to test the effect of information transparency, modernization of tax service technology, and tax sanctions against individual taxpayer compliance. Independent variables in this study are information transparency, modernization of tax service technology, and tax sanctions, while the dependent variable is individual taxpayer compliance. This research uses primary data by handing out questionnaires to the taxpayer. 380 questionnaires had been handed out to private taxpayers in KPP Pratama Jakarta Sunter, The method used in the research is convenience sampling. Data analytic used multiple regression analytics data. This study indicates that information transparency, modernization of tax service technology, and tax sanctions positively affect individual taxpayer compliance.